Positive electrode active material for lithium secondary battery, its manufacturing method, and lithium secondary battery including the same
By using secondary particles of primary macro particles coated with lithium boron oxide and controlling surface area, the active material addresses particle cracking and stability issues, enhancing capacity retention and life characteristics in lithium secondary batteries.
Patent Information
- Application Number
- JP2023531092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-11-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-11-30
AI Technical Summary
Conventional lithium secondary battery positive electrode active materials face issues with particle cracking, high surface area leading to side reactions, and decreased stability due to the use of secondary particles and high-nickel content, which affects capacity retention and thermal stability.
A positive electrode active material comprising secondary particles made of primary macro particles with an average diameter of 1 μm or more, coated with lithium boron oxide, and a specific surface area controlled to 0.2 to 1.25 m^2/g, with a BET change rate of 70% or less during rolling, ensuring reduced particle cracking and improved capacity retention.
The solution provides a positive electrode active material with enhanced capacity maintenance and improved life characteristics by controlling BET changes and minimizing particle cracking during the rolling process.
Smart Images

Figure 0007621484000004 
Figure 0007621484000005 
Figure 0007621484000006
Abstract
Description
[Technical Field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery containing primary giant particles and a method for producing the same.
[0002] This application claims priority based on Korean Patent Application No. 10-2020-0164872, filed on November 30, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings thereof. [Background technology]
[0003] In recent years, with the rapid spread of battery-powered electronic devices such as mobile phones, laptops, and electric vehicles, there has been a surge in demand for secondary batteries that are small, lightweight, and have relatively high capacity. In particular, lithium secondary batteries, which are lightweight and have high energy density, have attracted attention as power sources for portable devices. Therefore, active research and development is being conducted to improve the performance of lithium secondary batteries.
[0004] In a lithium secondary battery, an organic or polymer electrolyte solution is filled between a positive electrode and a negative electrode, which are made of active materials that allow lithium ions to be intercalated and deintercalated. Chemical energy is converted into electrical energy through oxidation and reduction reactions that occur when lithium ions are intercalated and deintercalated at the positive and negative electrodes.
[0005] Positive electrode active materials used in lithium secondary batteries include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), and lithium iron phosphate (LiFePO4). Among these, lithium cobalt oxide (LiCoO2) is widely used as a high-voltage positive electrode active material due to its advantages of high operating voltage and excellent capacity characteristics. However, rising cobalt (Co) prices and unstable supply limit its mass use as a power source in fields such as electric vehicles. Therefore, the development of alternative positive electrode active materials is needed. To address this issue, nickel-cobalt-manganese-based lithium composite transition metal oxides (hereinafter simply referred to as "NCM-based lithium composite transition metal oxides"), in which a portion of the cobalt (Co) is replaced with nickel (Ni) and manganese (Mn), have been developed.
[0006] On the other hand, previously developed NCM-based lithium composite transition metal oxides are in the form of secondary particles formed by agglomeration of primary microparticles, resulting in a large specific surface area and low particle strength. Furthermore, when an electrode is manufactured using a cathode active material containing these secondary particles formed by agglomeration of primary microparticles and then rolled, severe particle cracking can occur, resulting in significant gas generation during cell operation and reduced stability. In particular, in the case of NCM-based lithium composite transition metal oxides with a high nickel (Ni) content, which have an increased Ni content to ensure high capacity, structural and chemical stability is further reduced, and thermal stability is also difficult to ensure.
[0007] To address these issues, monoliths have been researched and developed. Monoliths are particles that exist independently of the secondary particles and have no apparent grain boundaries. Compared to secondary particles, which are formed by agglomeration of fine primary particles, monoliths have a lower BET and a reduced surface reactive site, reducing side reactions with the electrolyte. This provides advantages in controlling side reactions and ensuring stability. However, these monoliths have problems with increased resistance and reduced capacity retention due to the reduced BET and the rock salt structure formed on the surface during high-temperature firing. Summary of the Invention [Problem to be solved by the invention]
[0008] The problem to be solved by the present invention is to provide a positive electrode active material with improved capacity retention by controlling the BET change during the rolling process.
[0009] This reduces particle cracking during rolling of the positive electrode active material, thereby providing a nickel-based positive electrode active material with improved life characteristics. [Means for solving the problem]
[0010] One aspect of the present invention provides the following positive electrode active material.
[0011] in particular, A positive electrode active material for a lithium secondary battery, comprising at least one secondary particle comprising an aggregate of primary macroparticles, The primary large particles have an average particle size (D50) of 1 μm or more, a part or all of the surfaces of the secondary particles or the primary macroparticles are coated with lithium boron oxide; The average particle size (D50) of the secondary particles is 3 to 6 μm, The electrode containing the positive electrode active material has a specific surface area of 0.2 to 1.25 m before being rolled. 2 / g, The present invention provides a positive electrode active material for a lithium secondary battery, in which the BET change rate of the positive electrode active material is 70% or less before and after rolling an electrode containing the positive electrode active material.
[0012] At this time, the rolling conditions for the electrode are such that the porosity of the electrode becomes 15 to 30%, more specifically, 25%.
[0013] The BET change rate of the positive electrode active material may be 50% or less before and after rolling an electrode including the positive electrode active material.
[0014] The specific surface area of the positive electrode active material after rolling is 1.5 m 2 / g or less.
[0015] The positive electrode active material may have a PSD distribution of particles smaller than 1 μm of less than 5% when recovered under conditions that result in an electrode porosity of 15 to 30%. The primary giant particles may have an average particle size (D50) of 2 μm or more, and the ratio of the average particle size (D50) of the primary giant particles to the average crystal size of the primary giant particles may be 2 or more.
[0016] In the positive electrode active material, the primary giant particles may fall off from the secondary particles during rolling, and the fallen primary giant particles themselves may not be cracked.
[0017] The primary macroparticles may have an average crystallite size of 150 nm or greater.
[0018] The ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary macroparticles may be 2-4.
[0019] The positive electrode active material may include a nickel-based lithium transition metal oxide.
[0020] The nickel-based lithium transition metal oxide is Li (1+a) Ni (1-(a+x+y+w)) Co x M1 y M2 w O2 (wherein 0≦a≦0.5, 0≦x≦0.35, 0≦y≦0.35, 0≦w≦0.1, 0≦a+x+y+w≦0.7, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).
[0021] The amount of boron in the lithium boron oxide may be 0.05 to 0.2% by mass based on the total weight of the positive electrode active material.
[0022] Another aspect of the present invention provides a positive electrode for a lithium secondary battery, including the above-described positive electrode active material.
[0023] Yet another aspect of the present invention provides a lithium secondary battery including the above-described positive electrode active material.
[0024] Yet another aspect of the present invention provides a method for manufacturing a positive electrode active material according to the following embodiment.
[0025] (S1) synthesizing a precursor containing nickel, cobalt, and manganese through a coprecipitation reaction; (S2) mixing a precursor containing nickel, cobalt, and manganese with a lithium source material and a doping element, and then heat treating the mixture to prepare a nickel-based lithium transition metal oxide; (S3) mixing the nickel-based lithium transition metal oxide with a boron compound and then heat-treating the mixture to coat the surface of the nickel-based lithium transition metal oxide with lithium boron oxide; A method for producing a positive electrode active material, comprising: The positive electrode active material is at least one secondary particle comprising an agglomerate of up to 10 primary macroparticles; The primary large particles have an average particle size (D50) of 1 μm or more, a part or all of the surfaces of the secondary particles or the primary macroparticles are coated with lithium boron oxide; The average particle size (D50) of the secondary particles is 3 to 15 μm, The specific surface area of the positive electrode active material before rolling is 0.2 to 1.25 m 2 / g, The present invention provides a method for producing a positive electrode active material for a lithium secondary battery, in which the BET change rate before / after rolling of the positive electrode active material is 70% or less.
[0026] The step (S1) may be performed at pH 7 to pH 10, the step (S2) may be performed at 800 to 900°C, and the step (S3) may be performed at 300 to 400°C.
[0027] The boron compound may be any one selected from the group consisting of B(OH)3, B2O3, H3BO3, B2O5, LiBO3, Li2B4O7, and Na2B4O7, or a mixture of two or more thereof.
[0028] The step (S1) may be carried out under conditions of pH 7 to pH 10. [Effects of the Invention]
[0029] According to one aspect of the present invention, it is possible to provide a positive electrode active material with improved capacity retention rate by controlling the BET change during the rolling process.
[0030] According to one aspect of the present invention, by controlling the firing temperature and coating at least a portion of the surface of the secondary particles, particle cracking and the amount of fine powder generated during rolling are suppressed, thereby providing a positive electrode active material with significantly improved life characteristics.
[0031] The drawings attached to this specification illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters depicted in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated to emphasize a clearer description. [Brief explanation of the drawings]
[0032] [Figure 1] This is an SEM photograph of secondary particles containing primary fine particles. [Figure 2] This is an SEM photograph of a single particle. [Figure 3] This is an SEM photograph of secondary particles including large primary particles. DETAILED DESCRIPTION OF THE INVENTION
[0033] Hereinafter, embodiments of the present invention will be described in detail. Prior to this, the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts corresponding to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best explain the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not represent the entire technical ideas of the present invention, and therefore, various equivalents and modifications that can be substituted therefor may exist at the time of filing this application.
[0034] Throughout this specification, when a part "comprises" another component, it does not mean excluding the other component, but may further include the other component, unless otherwise specified.
[0035] In this specification and claims, "comprising a large number of crystal grains" refers to a crystalline body consisting of two or more crystal grains with a specific average crystal size. The crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction (XRD) analysis using CuKα X-rays. Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder, irradiating the particles with X-rays, and analyzing the resulting diffraction pattern. Sampling is performed by placing the sample in the central groove of a standard powder holder, and using a glass slide to make the surface uniform and level with the holder's periphery. The sample is measured using a Bruker D8 Endeavor (CuKα, λ = 1.54 Å) equipped with a LynxEye XE-T position detector, with an FDS of 0.5°, a 2θ range of 15° to 90°, a step size of 0.02°, and a total scan time of 20 minutes. The measured data is subjected to Rietveld refinement, taking into account the charge at each site (metals at the transition metal site are +3, Ni at the Li site is +2) and cation mixing. For crystal size analysis, instrumental broadening is considered using the Fundamental Parameter Approach (FPA) implemented in Bruker's TOPAS program, and the entire peak in the measurement range is used for fitting. Peak morphology is fitted using only the Lorenzian contribution in the First Principle (FP) peak type available in TOPAS, without considering strain. Through this method, structural analysis can be performed, allowing for quantitative analysis of the average crystal size of the crystal grains.
[0036] In this specification and claims, D50 may be defined as the particle size at 50% of the particle size distribution and may be measured using a laser diffraction method. For example, the average particle size (D50) of the positive electrode active material may be measured by dispersing particles of the positive electrode active material in a dispersion medium, introducing the dispersed particles into a commercially available laser diffraction particle size analyzer (e.g., MT3000 manufactured by Microtrac), irradiating the dispersed particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the cumulative volume in the analyzer.
[0037] In the present invention, the term "primary particles" refers to particles that do not appear to have grain boundaries when observed under a scanning electron microscope at a magnification of 5,000 to 20,000. Primary particles can be classified into primary microparticles and primary macroparticles depending on their average particle size (D50).
[0038] In the present invention, the "secondary particles" are particles formed by agglomeration of the primary particles.
[0039] In the present invention, the term "single particle" refers to a particle that exists independently of the secondary particles and has no apparent grain boundary, for example, a particle having a particle size of 0.5 μm or more.
[0040] In the present invention, the term "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.
[0041] <Cathode active material> One aspect of the present invention provides a positive electrode active material in a secondary particle form that is different from conventional ones.
[0042] in particular, 1) A positive electrode active material for a lithium secondary battery, comprising at least one secondary particle comprising an aggregate of primary macroparticles, 2) The primary large particles have an average particle size (D50) of 1 μm or more, 3) A part or all of the surfaces of the secondary particles are coated with lithium boron oxide, 4) The average particle size (D50) of the secondary particles is 3 to 15 μm, 5) The specific surface area of the positive electrode active material before rolling the electrode containing the positive electrode active material is 0.2 to 1.25 m 2 / g, The present invention provides a positive electrode active material for a lithium secondary battery, in which when an electrode containing the positive electrode active material is rolled, the BET change rate of the positive electrode active material before and after rolling is 70% or less.
[0043] At this time, the rolling conditions for the electrode are such that the porosity of the electrode becomes 15 to 30%.
[0044] The secondary particles have the above characteristics 1) to 5), and thus can provide a nickel-based positive electrode active material with improved life characteristics.
[0045] The properties 1) to 5) possessed by the secondary particles will be explained in detail below.
[0046] <Particle morphology and primary macroparticles> Generally, nickel-based lithium transition metal oxides are in the form of secondary particles, which may be in the form of agglomerates of primary particles.
[0047] Specifically, dense nickel-based lithium transition metal hydroxide secondary particles prepared by coprecipitation are used as a precursor. The precursor is mixed with a lithium precursor and calcined at a temperature below 960°C to obtain nickel-based lithium transition metal oxide secondary particles. Such conventional secondary particles are shown in Figure 1. However, when a cathode active material containing conventional secondary particles is applied to a current collector and then rolled, the particles themselves crack, increasing their specific surface area. This increased specific surface area can lead to problems such as increased side reactions with the electrolyte.
[0048] To address these issues, a new cathode active material made of single particles has been developed. Specifically, by increasing the calcination temperature compared to the synthesis conditions for conventional cathode materials, a single-particle nickel-based lithium transition metal oxide can be obtained without further secondary particle formation. Figure 2 shows such a single-particle cathode active material. However, single particles have a significantly reduced surface area compared to conventional secondary particles, which can lead to increased resistance due to the reduced reaction area. Furthermore, larger single particles can increase the diffusion distance of lithium ions, resulting in increased diffusion resistance.
[0049] One aspect of the present invention is to solve such problems.
[0050] When a high-density precursor is fired at a high firing temperature, as in the past, it is inevitable that not only the average particle size (D50) of the primary particles but also the average particle size (D50) of the secondary particles will increase. However, when the above-mentioned problems of surface and diffusion resistance occur, the firing temperature must be slightly lowered to control the degree of mono-particle formation. In this case, as the size of the primary particles decreases, the growth of the secondary particles also decreases, making it difficult to simultaneously control the size of the secondary particles and the size of the primary particles.
[0051] Meanwhile, the secondary particles according to one embodiment of the present invention are different from the conventional single particle obtaining method in the following points.
[0052] As described above, conventional single particles were formed by simply using a conventional secondary particle precursor and increasing the primary firing temperature. In contrast, secondary particles according to one embodiment of the present invention use a separate precursor with high porosity. When the porosity is high, increasing the firing temperature to form single particles can limit the growth of primary particles and simultaneously limit the growth of secondary particles. This method allows for the same level of secondary particle size control under similar firing conditions as when conventional secondary particle precursors are used to form single particles by increasing the firing temperature, but allows for a smaller primary particle size compared to conventional single particles. This allows for the production of cathode materials with higher BET, surface resistance, and diffusion resistance than conventional single particles.
[0053] As a result, the secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional secondary particles, but the average particle size (D50) of the primary particles is larger. That is, unlike the general morphology of conventional cathode active materials, i.e., a secondary particle formed by the aggregation of primary particles with small average particle size, the secondary particle morphology is provided by the aggregation of primary large particles that are larger than the primary particles. Such a single-particle cathode active material is shown in Figure 3.
[0054] In the present invention, "primary large particles" are those having an average particle size (D50) of 1 μm or more.
[0055] In a specific embodiment of the present invention, the average particle size of the primary large particles may be 1 μm or more, 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, or 3.5 μm or more, and may be 5 μm or less, 4.5 μm or less, or 4 μm or less. If the average particle size of the primary large particles is less than 1 μm, the secondary particles formed by agglomeration of these particles correspond to conventional secondary small particles, which may cause particle cracking during rolling.
[0056] In the present invention, the "primary large particles" have a ratio of average particle diameter (D50) to average crystal size of 3 or more. That is, compared to primary fine particles that constitute conventional secondary particles, the primary large particles are primary particles in which the average particle diameter and average crystal size have grown simultaneously.
[0057] That is, the primary large particles in the present invention refer to particles that have a large average crystal size as well as a large average particle size, and do not appear to have grain boundaries.
[0058] Thus, compared to conventional single particles, the "secondary small particles composed of aggregates of primary large particles" used in one embodiment of the present invention are advantageous in that the surface resistance and internal diffusion resistance are reduced due to an increase in BET and a decrease in primary particle size.
[0059] The average crystal size of the primary macroparticles can be quantitatively analyzed using X-ray diffraction (XRD) analysis using CuKα X-rays. Specifically, the produced particles are placed in a holder, and the diffraction pattern generated by irradiating the particles with X-rays is analyzed to quantitatively analyze the average crystal size of the primary macroparticles. The sample is placed in the central groove of a standard powder holder, and a glass slide is used to smooth the surface and align the height with the holder's periphery. The sample is measured using a Bruker D8 Endeavor (CuKα, λ = 1.54 Å) equipped with a LynxEye XE-T position detector, with FDS 0.5°, a 2θ range of 15° to 90°, a step size of 0.02°, and a total scan time of 20 minutes. The measured data are then subjected to Rietveld analysis, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing at each site. During crystal size analysis, instrumental broadening is taken into account using the Fundamental Parameter Approach (FPA) implemented in Bruker's TOPAS program, and the entire peak in the measurement range is used during fitting. Peak morphology is fitted using only the Lorenzian contribution in the First Principle (FP) peak type available in TOPAS, without considering strain. This method allows for structural analysis and quantitative analysis of the average crystal size of the crystal grains.
[0060] In a specific embodiment of the present invention, the ratio of the average particle diameter (D50) to the average crystal size may be 2 or more, 2.5 or more, 3 or more, and 50 or less, 40 or less, 35 or less.
[0061] Additionally, the average crystallite size of the primary macroparticles can be 150 nm or more, 170 nm or more, 200 nm or more, and 300 nm or less, 270 nm or less, or 250 nm or less.
[0062] <Secondary particles> The secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional primary particles, but have a larger average particle size (D50) than conventional cathode active materials. That is, unlike the general morphology of conventional cathode active materials, in which secondary particles are formed by agglomeration of small primary particles, the secondary particles are formed by agglomeration of large primary particles that are larger than the primary particles.
[0063] In one specific embodiment of the present invention, the secondary particles may be formed by agglomeration of 1 to 10 of the primary giant particles. More specifically, the secondary particles may be formed by agglomeration of 1 or more, 2 or more, 3 or more, or 4 or more of the primary giant particles within the above-mentioned numerical range, and may be formed by agglomeration of 10 or less, 9 or less, 8 or less, or 7 or less of the primary giant particles within the above-mentioned numerical range.
[0064] The secondary particles according to one embodiment of the present invention have an average particle size (D50) of 3 μm to 6 μm, more specifically, 3 μm or more, 3.5 μm or more, 4 μm or more, or 4.5 μm or more, and 6 μm or less, 5.5 μm or less, or 5 μm or less.
[0065] Generally, regardless of particle morphology, for the same composition, as the calcination temperature increases, the particle size and the average crystal size within the particle increase. On the other hand, in one embodiment of the present invention, by using a porous precursor, primary large particles with large diameters can be grown even under calcination conditions similar to those used in conventional single particle synthesis, while secondary small particles can be controlled to a similar level as conventional.
[0066] Therefore, the secondary particles according to one aspect of the present invention are composed of primary macroparticles that have the same or similar average particle size (D50) as conventional secondary particles, but have larger average particle size and average crystal size than conventional primary fine particles.
[0067] In a specific embodiment of the present invention, the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary large particles may be 2-4.
[0068] On the other hand, in the present invention, the specific surface area of the positive electrode active material before rolling the electrode containing the positive electrode active material is 0.2 to 1.25 m 2 / g, and the BET change rate of the positive electrode active material is 70% or less, more specifically 50% or less, before and after rolling of an electrode containing the positive electrode active material.
[0069] The inventors have confirmed that the capacity retention rate of the secondary particles according to the present invention varies depending on the BET (specific surface area). Specifically, in one aspect of the present invention, they confirmed that when a material exhibits a large BET change before and after rolling, the surface of the cathode active material that is not treated with lithium boron oxide during rolling is exposed to the outside, resulting in severe side reactions with the electrolyte. They also confirmed that physical contact between secondary particles leads to poor electrochemical performance. To reduce this BET change, the present invention coats at least a portion or all of the secondary particles with lithium boron oxide. The lithium boron oxide is formed by mixing a boron compound, such as B(OH)3, BO, HBO, BO, LiBO, LiBO, NaBO, or other boron compounds with a cathode active material and then firing the mixture in an oxygen atmosphere. This lithium boron oxide is the result of lithium impurities remaining in the cathode active material reacting with the boron compound in an oxygen atmosphere. The amount of boron in the lithium boron oxide may be 0.05 to 0.2% by mass based on the total weight of the positive electrode active material.
[0070] Meanwhile, the inventors have also confirmed that the capacity retention rate changes depending on the generation of PSD fine powder. Specifically, in one aspect of the present invention, they confirmed that in materials with large PSD changes before and after rolling, the surface of the cathode active material that is not treated with a boron compound during rolling is exposed to the outside, exacerbating side reactions with the electrolyte. They also confirmed that physical contact between secondary particles leads to poor electrochemical performance. In order to reduce the occurrence of such PSD changes, the present invention aims to provide a cathode active material with a low PSD change rate by controlling the sintering temperature and coating at least a portion of the surface of the secondary particles.
[0071] Accordingly, the cathode active material coated with the lithium boron oxide is rolled to a porosity of 15% to 30% to prepare the cathode active material, and after rolling, the content of fine particles of 1 μm or less may be less than 5%, more specifically less than 2.5%, and most specifically less than 2%.
[0072] In this case, when the secondary particles are rolled, the primary macroparticles fall off and do not crack. The rolling conditions may be such that the electrode porosity is 15% to 30%. More specifically, the electrode porosity may be 25%.
[0073] <Composition> The secondary particles contain a nickel-based lithium transition metal oxide.
[0074] At this time, the nickel-based lithium transition metal oxide is Li (1+a) Ni (1-(a+x+y+w)) Co x M1 y M2 w O2 (wherein 0≦a≦0.5, 0≦x≦0.35, 0≦y≦0.35, 0≦w≦0.1, 0≦a+x+y+w≦0.7, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).
[0075] In the above formula, a, x, y, and w represent the molar ratio of each element in the nickel-based lithium transition metal oxide.
[0076] In this case, the metals M1 and M2 doped into the crystal lattice of the secondary particles may be located only on a portion of the surface of the particle, or may be located with a concentration gradient that decreases from the surface toward the center of the particle, or may be present uniformly throughout the particle, depending on the location preference of the element M1 and / or the element M2.
[0077] When the secondary particles are doped or coated and doped with metals M1 and M2, the long life characteristics of the active material can be further improved, particularly due to stabilization of the surface structure.
[0078] <Positive electrodes and lithium secondary batteries> According to yet another aspect of the present invention, there are provided a positive electrode for a lithium secondary battery and a lithium secondary battery, each containing the positive electrode active material.
[0079] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0080] The positive electrode current collector in the positive electrode is not particularly limited as long as it does not induce chemical changes in the battery and is conductive. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The positive electrode current collector typically has a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to enhance adhesion of the positive electrode active material. It may be used in various forms, such as a film, sheet, foil, net, porous material, foam, or nonwoven fabric.
[0081] The positive electrode active material layer may include a conductive material and a binder in addition to the above-described positive electrode active material.
[0082] The conductive material is used to impart conductivity to the electrode and can be any material that is electronically conductive and does not cause chemical changes in the battery. Specific examples include graphite, such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, or silver; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; and conductive polymers, such as polyphenylene derivatives. These materials may be used alone or in combination. The conductive material is typically contained in an amount of 1 to 30 wt % based on the total weight of the positive electrode active material layer.
[0083] The binder also serves to improve adhesion between positive electrode active material particles and between the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof. These binders may be used alone or in combination. The binder may be included in an amount of 1 to 30 wt % based on the total weight of the positive electrode active material layer.
[0084] The positive electrode may be fabricated by a conventional method for fabricating a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be fabricated by coating a positive electrode active material layer-forming composition containing the positive electrode active material and, optionally, a binder and a conductive material, on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.
[0085] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that allows excellent thickness uniformity to be achieved during subsequent coating for manufacturing a positive electrode.
[0086] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0087] According to yet another aspect of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0088] The lithium secondary battery may further include a battery case that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery case.
[0089] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0090] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. may be used. The negative electrode current collector typically has a thickness of 3 μm to 500 μm. As with the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to enhance adhesion of the negative electrode active material. The negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous material, foam, or nonwoven fabric.
[0091] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material. For example, the negative electrode active material layer may be fabricated by coating a negative electrode-forming composition including the negative electrode active material and, optionally, the binder and the conductive material on a negative electrode current collector and drying the coating, or by casting the negative electrode-forming composition on a separate support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector.
[0092] The negative electrode active material may be a compound capable of reversible lithium intercalation and deintercalation. Specific examples thereof include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; and SiO. βExamples of suitable materials include metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide (0<β<2); or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites. These materials may be used alone or in combination. A thin film of metallic lithium may also be used as the negative electrode active material. Examples of suitable carbonaceous materials include low-crystalline carbon and high-crystalline carbon. Examples of suitable low-crystalline carbon include soft carbon and hard carbon. Examples of suitable high-crystalline carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitch, and high-temperature-calcined carbon, such as petroleum- or coal-based coke.
[0093] The binder and conductive material are the same as those described above for the positive electrode.
[0094] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and positive electrode and provides a path for lithium ions to move. Any separator commonly used in lithium secondary batteries can be used without limitation. In particular, a separator with low resistance to electrolyte ion movement and excellent electrolyte impregnation capacity is preferred. Specifically, a porous polymer film, such as a porous polymer film made from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof, can be used. Conventional porous nonwoven fabrics, such as nonwoven fabrics made from high-melting-point glass fibers or polyethylene terephthalate fibers, can also be used. To ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material can be used, and can be used in a single-layer or multi-layer structure.
[0095] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in manufacturing lithium secondary batteries, but are not limited to these.
[0096] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0097] The organic solvent may be any suitable medium for ion migration in the electrochemical reaction of the battery. Examples of suitable organic solvents include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a C2-C20 linear, branched, or cyclic hydrocarbon group that may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) with a high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are preferably mixed in a volume ratio of about 1:1 to about 1:9, which provides excellent electrolyte performance.
[0098] The lithium salt may be any compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0 M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate conductivity and viscosity, exhibiting excellent electrolyte performance and allowing for efficient lithium ion migration.
[0099] In addition to the electrolyte components described above, the electrolyte may further include one or more additives, such as haloalkylene carbonate compounds (e.g., difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purposes of improving battery life characteristics, suppressing battery capacity reduction, and improving battery discharge capacity. In this case, the additives may be included in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0100] A lithium secondary battery containing the positive electrode active material according to the present invention is useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0101] According to yet another aspect of the present invention, there are provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0102] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0103] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in various different forms and is not limited to the exemplary embodiments described below.
[0104] Example 1 A coprecipitation reactor (20 L capacity) was charged with 4 L of distilled water, and 100 mL of 28 wt% aqueous ammonia was added while maintaining the temperature at 50°C. A 3.2 mol / L transition metal solution (NiSO4, CoSO4, and MnSO4 mixed at a nickel:cobalt:manganese molar ratio of 0.8:0.1:0.1) was then continuously added at 300 mL / hr and 28 wt% aqueous ammonia at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9. The coprecipitation reaction was carried out for 10 hours to form precursor particles. The precursor particles were separated, washed, and then dried in an oven at 130°C to produce the precursor.
[0105] Ni synthesized by coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was mixed with Li2CO3 so that the Li / Me(Ni, Co, Mn) molar ratio was 1.05, and then heat-treated at 850°C for 10 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 A positive electrode active material containing O2-lithium composite transition metal oxide was produced.
[0106] The prepared cathode active material containing the lithium composite transition metal oxide was mixed with H3BO3 as a boron compound and heat-treated at 400°C for 10 hours in an air atmosphere to prepare a surface-coated cathode active material. The amount of H3BO3 mixed was 1% by mass of the cathode active material containing the lithium composite transition metal oxide.
[0107] <Example 2> In Example 2, a positive electrode active material was prepared in the same manner as in Example 1, except that the amount of H3BO3 mixed was adjusted to 0.5% by mass based on the positive electrode active material containing the lithium composite transition metal oxide.
[0108] <Comparative Example 1> In Comparative Example 1, a positive electrode active material was produced in the same manner as in Example 1, except that the heat treatment temperature when producing the lithium composite transition metal oxide was lowered to 830° C. In this case, the secondary particles of the present invention were not formed.
[0109] <Comparative Example 2> In Comparative Example 2, a positive electrode active material was produced in the same manner as in Example 1, except that H3BO3 was not coated.
[0110] [Experimental Example 1: Comparison of BET changes due to rolling depending on composition] In the present invention, the BET change rate due to rolling of the electrode was measured by the following method.
[0111] Each positive electrode active material prepared in the Examples and Comparative Examples, a carbon black conductive material, and a PVdF binder were mixed in a weight ratio of 96:2:2 in N-methylpyrrolidone solvent to prepare a positive electrode slurry, which was then coated on one side of an aluminum current collector and dried at 100°C to prepare a pre-rolled positive electrode. This electrode was rolled to a porosity of 25% to prepare a post-rolled positive electrode.
[0112] The prepared pre-rolled and post-rolled positive electrodes were heat-treated in air at 500°C for 10 hours to remove the binder and conductive material. The remaining positive electrode active material powder was then collected and measured for particle size distribution. The results are shown in Table 1 below.
[0113] As can be seen from Table 1, in the case of Example 1, where the heat treatment temperature was higher than in Comparative Example 1, the BET change was small at 50%, and even in Example 2, where the amount of H3BO3 mixed was reduced to half, the BET change was about 70%, which is smaller than in Comparative Example 1. Furthermore, in the case of Comparative Example 2, where no coating treatment was performed compared to Example 1, the BET change was confirmed to be large at 110%, indicating that the BET change is small when the firing heat treatment temperature is high and a coating treatment is performed.
[0114] [Table 1]
[0115] [Experimental Example 2: Comparison of remaining capacity after 30 charge / discharge cycles depending on composition] Positive electrodes were fabricated using the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2 in the same manner as in Experimental Example 1, and the capacity retention rates were measured in the following manner.
[0116] Lithium metal was used as the negative electrode.
[0117] An electrode assembly was fabricated by interposing a porous polyethylene separator between the cathode and anode fabricated as described above, and the electrode assembly was placed inside a case. An electrolyte solution was then injected into the case to fabricate a lithium secondary battery. The electrolyte solution was prepared by dissolving 1.0 M lithium hexafluorophosphate (LiPF6) in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (EC / EMC / DEC mixed in a volume ratio of 3 / 4 / 3).
[0118] The fabricated lithium secondary battery half-cell was charged at 45°C in CC (constant current)-CV (constant voltage) mode at 0.7 C to 4.4 V and then discharged at a constant current of 0.5 C to 3.0 V, and the capacity retention rate was measured after 30 charge-discharge cycles to evaluate the lifespan characteristics. The results are shown in Table 2 below.
[0119] [Table 2]
[0120] In the case of Comparative Example 2 in which the BET change was 110% in Experimental Example 2, the 30-cycle charge-discharge capacity retention rate was at a level of 84%, while in the case of Comparative Example 1 in which the BET change was 90%, the capacity retention rate increased slightly to 91%, and in the cases of Examples 2 and 1 in which the BET changes were 70% and 50%, respectively, the capacity retention rates were 94% and 95%, respectively. It was confirmed that the smaller the BET change in Experimental Example 1, the better the charge-discharge capacity retention rate.
[0121] [Experimental Example 3: Ratio of fine powder less than 1 μm in the rolled state of the positive electrode according to the composition] A positive electrode was prepared in the same manner as in Experimental Example 1, and the prepared positive electrode was heat-treated in air at 500°C for 10 hours to remove the binder and conductive material. The remaining positive electrode active material powder was collected and measured for particle size distribution. The results are shown in Table 3 below.
[0122] [Table 3]
[0123] As can be seen from Table 3, in Examples 1 and 2, which had higher heat treatment temperatures than Comparative Example 1, the ratios of particles less than 1 μm were low at 1.5% and 2.3%, respectively. Experimental Examples 1 to 3 confirm that when the BET change rate before / after rolling is 70% or less and the ratio of particles less than 1 μm after rolling is less than 5%, the capacity retention rate is excellent.
Claims
1. A positive electrode active material for a lithium secondary battery comprising at least one secondary particle comprising an aggregate of a primary macroparticle, The primary macroparticles have an average particle size (D50) of 1 μm or more; a part or all of the surface of the secondary particles or the primary macroparticles is coated with lithium boron oxide; The average particle size (D50) of the secondary particles is 3 to 15 μm, The positive electrode active material, the carbon black conductive material, and the PVDF binder were mixed in a weight ratio of 96:2:2 in an N-methylpyrrolidone solvent to prepare a positive electrode slurry, and the positive electrode slurry was applied to one surface of an aluminum current collector and dried at 100° C. to prepare a pre-rolled electrode. The pre-rolled electrode was rolled to a porosity of 15 to 30% to prepare a rolled positive electrode. When the electrode including the positive electrode active material was rolled, the BET specific surface area of the positive electrode active material was 0.2 to 1.25 m. 2 / g, A positive electrode active material for a lithium secondary battery, wherein a rate of change in a BET specific surface area of the positive electrode active material before and after rolling of an electrode containing the positive electrode active material is 70% or less.
2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a rate of change in a BET specific surface area of the positive electrode active material before and after rolling of an electrode containing the positive electrode active material is 50% or less.
3. The BET specific surface area of the positive electrode active material after rolling is 1.5 m 2 The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the Mo content is 1 / g or less.
4. The positive electrode active material for a lithium secondary battery according to any one of claims 1 to 3, wherein the positive electrode active material is recovered under conditions in which the porosity of the electrode produced under the conditions according to claim 1 is 15 to 30%, and in a PSD distribution of the positive electrode active material, a ratio of particles having a size of less than 1 μm is less than 5%.
5. The primary macroparticles have an average particle size (D50) of 2 μm or more; 5. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of an average particle size (D50) of the primary large particles to an average crystal size of the primary large particles is 2 or more.
6. 6. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the primary giant particles fall off from the secondary particles when an electrode containing the positive electrode active material is rolled, and the fallen primary giant particles themselves do not crack.
7. 7. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the primary macroparticles have an average crystal size of 150 nm or more.
8. The positive electrode active material for lithium secondary batteries according to any one of claims 1 to 7, wherein the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary giant particles is 2 to 4.
9. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the positive electrode active material comprises a nickel-based lithium transition metal oxide.
10. The nickel-based lithium transition metal oxide is Li (1+a) Ni (1-(a+x+y+w)) Co x M1 y M2 w O 2 (wherein 0≦a≦0.5, 0≦x≦0.35, 0≦y≦0.35, 0≦w≦0.1, 0≦a+x+y+w≦0.7, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).
11. The positive electrode active material for lithium secondary batteries according to any one of claims 1 to 10, wherein the amount of boron in the lithium boron oxide is 0.05 to 0.2 mass% based on the total weight of the positive electrode active material.
12. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1.
13. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to claim 1.
14. A method for producing a positive electrode active material for a lithium secondary battery, comprising: (S1) synthesizing a precursor containing nickel, cobalt and manganese through a coprecipitation reaction; (S2) mixing a precursor containing nickel, cobalt and manganese with a lithium source material and a doping element, and then heat treating the mixture to prepare a nickel-based lithium transition metal oxide; (S3) mixing the nickel-based lithium transition metal oxide with a boron compound and then heat-treating the mixture to coat the surface of the nickel-based lithium transition metal oxide with lithium boron oxide; The positive electrode active material is at least one secondary particle comprising an agglomerate of a primary macroparticle; The primary macroparticles have an average particle size (D50) of 1 μm or more; a part or all of the surface of the secondary particles or the primary macroparticles is coated with lithium boron oxide; The average particle size (D50) of the secondary particles is 3 to 15 μm, The positive electrode active material, the carbon black conductive material, and the PVDF binder were mixed in a weight ratio of 96:2:2 in N-methylpyrrolidone solvent to prepare a positive electrode slurry, and the positive electrode slurry was applied to one side of an aluminum current collector and dried at 100° C. to prepare a pre-rolled electrode. The pre-rolled electrode was rolled to a porosity of 15 to 30% to prepare a rolled positive electrode. The BET specific surface area of the positive electrode active material before rolling was 0.2 to 1.25 m 2 / g, The method for producing a positive electrode active material for a lithium secondary battery, wherein a rate of change in BET specific surface area before and after rolling of the positive electrode active material is 70% or less.
15. The step (S1) is carried out at a pH of 7 to 10; The step (S2) is carried out at 800° C. to 900° C. The method of claim 14, wherein step (S3) is performed at 300° C. to 400° C.
16. The boron compound is B(OH). 3 , B 2 O 3 , H 3 B.O. 3 , B 2 O 5 , LiBO 3 , Li 2 B 4 O 7 and Na 2 B 4 O 7 The method for producing a positive electrode active material according to claim 14 or 15, wherein the positive electrode active material is any one selected from the group consisting of:
17. The method for producing a positive electrode active material according to any one of claims 14 to 16, wherein the step (S1) is carried out under a pH condition of 7 to 10.
Citation Information
Patent Citations
Cathode active material, method of producing the same, and cathode and lithium secondary battery employing the same
JP2015018803A
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2018073481A
Manufacturing method for positive electrode for non-aqueous electrolyte secondary battery and manufacturing method for non-aqueous electrolyte secondary battery
JP2019175721A
Positive electrode active material for lithium secondary battery and method for producing same
JP2020515010A
Positive electrode active material for secondary battery, method for producing the same, and positive electrode for secondary battery including the same
JP2022510653A